Tinjauan Hukum Islam terhadap Penerapan Praktek Ju‘ālah Ternak Sapi dalam Mudarabah (Studi Kasus Desa Bontomanai Kecamatan Rilau Ale Kabupaten Bulukumba) : Islamic Law Review of the Application of the Practice of Ju‘ālah Cattle in Mudarabah (Case Study of Bontomanai Village, Rilau Ale Subdistrict, Bulukumba Regency) - Sam, Zulfiah; Syamsiah Nur; Risdayani, Risdayani; Srimustika, Srimustika (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
The Islamic economic system is very much needed as in the application of cooperation contracts and profit sharing in the field of animal husbandry, especially in villages that depend on cattle farming as a source of income. This research aims to analyse the application of mudarabah concept in cattle ju'ālah contract in Bontomanai Village, Rilau Ale Sub-district, Bulukumba Regency. This research uses qualitative field research with research approaches including normative, descriptive, and case study approaches. The results showed that the mechanism for implementing the cooperation contract in Bontomanai Village involves the investor who provides the mother cow and the mudarib who maintains it, the profit sharing is divided according to the initial agreement agreed by both parties. as for any losses, it will be fully borne by the owner of the capital, unless the loss is caused by the negligence of the mudarib. In the distribution of profits, both parties agree to share the results of 1 calf for the capital owner at the first birth of the mother cow and 1 calf for the farmer at the second birth of the mother cow. The practice of applying mudarabah with ju'ālah profit sharing is in accordance with the principles of Islamic law, as long as both parties comply with the initial agreement that has been agreed upon and are able to overcome the garar contained in this profit-sharing cooperation. The implications of this research are expected to contribute to the development of literature on the application of sharia contracts in the livestock sector and can be a reference for village communities that have the same potential, especially in mudarabah contracts with ju'ālah profit sharing contracts in cattle.